2018
DOI: 10.1039/c8cc00090e
|View full text |Cite
|
Sign up to set email alerts
|

Selective protein unfolding: a universal mechanism of action for the development of irreversible inhibitors

Abstract: High-throughput differential scanning fluorimetry of GFP-tagged proteins (HT-DSF-GTP) was applied for the identification of novel enzyme inhibitors acting by a mechanism termed: selective protein unfolding (SPU). Four different protein targets were interrogated with the same library to identify target-selective hits. Several hits selectively destabilized bacterial biotin protein ligase. Structure-activity relationship data confirmed a structure-dependent mechanism of protein unfolding. Simvastatin and altenusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The Davis Open Access Natural Product-Based Library consists of distinct compounds, the majority (53%) of which are natural products obtained primarily from Australian fungal, plant, and marine invertebrate sources (11)(12), as well as semi-synthetic natural product analogues (28%) and known commercial drugs or synthetic compounds inspired by natural products (19%). All compounds evaluated in this study were analyzed for purity prior to testing and shown to be > 95% pure.…”
Section: Chemical Libraries and Hit Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Davis Open Access Natural Product-Based Library consists of distinct compounds, the majority (53%) of which are natural products obtained primarily from Australian fungal, plant, and marine invertebrate sources (11)(12), as well as semi-synthetic natural product analogues (28%) and known commercial drugs or synthetic compounds inspired by natural products (19%). All compounds evaluated in this study were analyzed for purity prior to testing and shown to be > 95% pure.…”
Section: Chemical Libraries and Hit Compoundsmentioning
confidence: 99%
“…However, outside of computational studies, few natural products to date have been demonstrated to act on SARS-CoV-2 replication (10). To identify natural product-derived compounds that may inhibit entry across multiple SARS-CoV-2 variants, we developed an AlphaScreen-based RBD/ACE2 interaction assay to screen a pure compound library containing 512 natural products and derivatives sourced predominantly from plants, mushrooms and marine invertebrates of Australia, Papua New Guinea, and neighboring regions (11)(12). The top hits from this screen, which included the plant stilbenoids (-)-hopeaphenol, vatalbinoside A, and vaticanol B (Figure 1), were then assessed for in vitro mechanisms of action using SARS-CoV-2 pseudoviruses and antiviral efficacy using infectious SARS-CoV-2 variants encompassing parental and B.1.1.7 and B.1.351 variants.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, these are the first examples of the derivatization of a benzylisoquinoline using Diversinate TM C–H functionalization chemistry. This unique library has been added to the Davis open-access natural product-based library for future drug discovery and chemical biology evaluations [41].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the genus, Alternaria , is a prominent representative, although it is usually known as a plant pathogen [ 2 ]. Altenusin is the characteristic metabolite of Alternaria sp., with a biphenyl skeleton, and has been reported to have antioxidant, antimicrobial, cytotoxic, biotin protein ligase inhibitory, FXR agonist, and tau protein aggregation inhibitory activities [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. To date, more than 15 altenusin derivatives have been discovered from fungal origins.…”
Section: Introductionmentioning
confidence: 99%